The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1103/physreva.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Indications of Plasma Instabilities Induced by Laser Heating

Abstract: The detection of -100-keV x radiation and of directly back-scattered light is described for neodymium-glass-laser light pulses focused on a polyethylene target. These observations can be explained in terms of the nonlinear excitation of plasma waves by the laser light.We recently made some measurements of x rays and light reflection from a laser-produced plasma which suggest that plasma instabilities have been produced. Our neodymium laser, which includes a multipass glass-disk system, has been described elsew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…Using a Nd:glass laser, B€ uchl et al 72 observed a twocomponent x-ray spectrum with an $2-keV nonthermal component that disappeared (along with the neutrons) when a background gas was added. Shearer et al 98 irradiated plastic targets with a Nd:glass laser at $2 Â 10 14 W/cm 2 and found 100-keV x rays with a temperature T H $ 50 keV; they suggested the parametric decay instability as the cause. Olsen et al 99 reported 200-to 800-keV x rays, also from a Nd:glass laser.…”
Section: B Suprathermal Electronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a Nd:glass laser, B€ uchl et al 72 observed a twocomponent x-ray spectrum with an $2-keV nonthermal component that disappeared (along with the neutrons) when a background gas was added. Shearer et al 98 irradiated plastic targets with a Nd:glass laser at $2 Â 10 14 W/cm 2 and found 100-keV x rays with a temperature T H $ 50 keV; they suggested the parametric decay instability as the cause. Olsen et al 99 reported 200-to 800-keV x rays, also from a Nd:glass laser.…”
Section: B Suprathermal Electronsmentioning
confidence: 99%
“…10-11(b)], plastic targets were irradiated at LLNL by Shearer et al 98 at a comparable intensity of $2 Â 10 14 W/cm 2 and a wavelength of 1 lm. Bursts of reflected light were seen, with up to 3% of the incident laser power observed in the f/7 lens (4 half-angle).…”
Section: B Stimulated Brillouin Scattering (Sbs) and Crossbeam Energmentioning
confidence: 99%
See 1 more Smart Citation
“…A record of the nine-pass reflected intensitv is given in Ref. 108. Figure 93 shows the five-pass reflected intensity.…”
Section: Plasma Experimentsmentioning
confidence: 99%
“…A small fraction of the laser energy, however, is absorbed into hot -electrons [7,8,9]. These electrons have energies in the range of 20 -40 keV preheating the fusion capsule which in turn results in a reduced capsule compressibility.…”
Section: Introductionmentioning
confidence: 99%